Estimation of radiation gonadal doses for the American–Ukrainian trio study of parental irradiation in Chornobyl cleanup workers and evacuees and germline mutations in their offspring. (1st November 2021) - Chumak, Vadim; Bakhanova, Elena; Kryuchkov, Victor; Golovanov, Ivan; Chizhov, Konstantin; Bazyka, Dimitry; Gudzenko, Natalia; Trotsuk, Natalia; Mabuchi, Kiyohiko; Hatch, Maureen; Cahoon, Elizabeth K; Little, Mark P; et al.
Abstract: Radiation doses of parents exposed from the Chornobyl accident as cleanup workers or evacuees were estimated in the National Cancer Institute-National Research Center for Radiation Medicine trio (i.e. father, mother, offspring) study aimed at investigating the radiation effects on germline de novo mutations in children as well as other outcomes. Paternal (testes) and maternal (ovaries) gonadal doses were calculated along with associated uncertainty distributions for the following exposure pathways: (a) external irradiation during the cleanup mission, (b) external irradiation during residence in Pripyat, and (c) external irradiation and (d) ingestion of radiocesium isotopes, such as 134 Cs and 137 Cs, during residence in settlements other than Pripyat. Gonadal doses were reconstructed for 298 trios for the periods from the time of the accident on 26 April 1986 to two time points before the child's date of birth (DOB): 51 (DOB-51) and 38 (DOB-38) weeks. The two doses, DOB-51 and DOB-38 were equal (within 1 mGy) in most instances, except for 35 fathers where the conception of the child occurred within 3 months of exposure or during exposure. The arithmetic mean of gonadal DOB-38 doses was 227 mGy (median: 11 mGy, range 0–4080 mGy) and 8.5 mGy (median: 1.0 mGy, range 0–550 mGy) for fathers and mothers, respectively. Gonadal doses varied considerably depending on the exposure pathway, the highest gonadal DOB-38 doses being received during the cleanup mission (mean doses of 376 and 34 mGy, median of 144 and 7.4 mGy for fathers and mothers, respectively), followed by exposure during residence in Pripyat (7.7 and 13 mGy for mean, 7.2 and 6.2 mGy for median doses) and during residence in other settlements (2.0 and 2.1 mGy for mean, 0.91 and 0.81 mGy for median doses). Monte Carlo simulations were used to estimate the parental gonadal doses and associated uncertainties. The geometric standard deviations (GSDs) in the individual parental stochastic doses due to external irradiation during the cleanup mission varied from 1.2 to 4.7 (mean of 1.8), while during residence in Pripyat they varied from 1.4 to 2.8 (mean of 1.8), while the mean GSD in doses received during residence in settlements other than Pripyat was 1.3 and 1.4 for external irradiation and ingestion of radiocesium isotopes, respectively.